Nano-mechanical properties and onset of plasticity in Fe–Mn–Al–Ni–C duplex lightweight steel processed by high temperature compression - Mozumder Y.H.; Rakshit R.; Ghosh D.; Marandi L.; Mandal S. (My University, 2025)
In the present study, nano-indentation tests have been performed on the Fe–Mn–Al–Ni–C duplex lightweight steel following hot compression at 1223 K and 1423 K at a strain rate of 0.1 s−1. The nano-hardness values of various composite regions are determined and correlated with the complex deformed microstructural features, strain gradient, elemental partitioning, intergranular/intragranular precipitates and lattice distortion effect. The estimated elastic modulus value of FCC and BCC matrix regions in the studied steel is relatively higher than those reported for other conventional duplex steels, highlighting the contribution of intragranular B2 and к-carbide precipitates on the overall elastic modulus. Additionally, the deformation behavior of the matrix regions reveals that the onset of plasticity is governed by both homogeneous dislocation nucleation mechanism and multiplication of pre-existing dislocations under the indenter tip. The BCC + B2 region exhibits higher maximum shear stress (τmax) value as compared to the FCC + к-carbide region, indicating that the plastic deformation would first initiate in the latter region. This is related to the pre-existing high strain gradient in the soft FCC + к-carbide region that would facilitate the onset of plasticity more easily as compared to the BCC + B2 region during indentation. Moreover, it is observed that the elasto-plastic regime of the indentation loading curve exhibits random pop-in events associated with the resistance generated by the various intragranular precipitates in the FCC and BCC matrix regions, against the dislocation motion during nano-indentation test. © 2022 Elsevier B.V.